Invertebrates of Siberia, a potential source of animal protein for innovative food and feed production. 2. Nutrient composition of the two new model species - Sergei E. Tshernyshev; Irina B. Babkina; Ruslan T-O. Baghirov; Vera P. Modyaeva; Margarita D. Morozova; Ksenia E. Skriptcova; Elena Yu. Subbotina; Mikhail V. Shcherbakov; Anastasia V. Simakova (Acta Biologica Sibirica)
The use of terrestrial invertebrates occurring in Siberia as a source of nutrients as an innovative form of new quality food production in North Asia is analysied. Two species, big slug Limacus flavus (Linnaeus, 1758) and rose chafer Cetonia aurata viridiventris Reitter, 1896 have been reared under laboratory conditions and prepared for nutrient analysis. Biomass have been taken from the instar stages of slugs and beetle larvae, animals have been killed by frozen and then presented for analysis. To determine the nutritive value, following macro- and micro- nutrients and dietary fibre have been revealed and determined from the biomass: В1 (thiamine), В2 (riboflavin), B3 (nicotinamide), B6 (pyridoxine), В9 (folacin), B12 (cyanocobalamin), Е (α- tocopherol), А (retinol palmitate), Fe, Se, Zn, Mn, Cu, Mg, F, lipid, protein, carbohydrate and chitin. In slugs and beetle larvae the mass fraction of protein is 20.6 and 20.8%, the fat percentage is 0.43 and 0.44%, and carbohydrate is 0.22 and 0.27%. Caloricity varied from 98 kilocalories in slugs to 96 in beetle larvae. All species are rich in magnesium (160 mg/100 g and 288 mg/100 g) and phosphorus (320 mg/100 g and 450 mg/100 g) (these elements are represented as macronutrients), and contains high level of iron (3.3 mg/100 g and 5.1 mg/100 g), copper (0.50 mg/100 g and 1.6 mg/100 g), selenium (0.0235 mg/100 g and 0.0334 mg/100 g), zinc (0.80 mg/100 g and 1.9 mg/100 g) and manganese (0.0076 mg/100 g and 0.0112 mg/100 g). Four vitamins detected, namely: А (0.0225 mg/100 g and 0.0337 mg/100 g), E (5.2 mg/100 g and 0.59 mg/100 g), В1 (2.5 mg/100 g) и В2 (5.2 mg/100 g and 0.59 mg/100 g). Almost completely lacking B3, B6, B9 and B12. Biomass both slugs and beetles is similar by nutrient composition and differs in presence of vitamin B3 in slugs, and 1.5 time higher vitamin A content in beetle larvae. The data revealed from the two terrestrial invertebrates show high level of natural nutrients, that could be used for food production, and in combination with not difficult raising hese species are perspective for farming in local conditions of different countries, excepting extremely hot and arid regions. Perspectives of terrestrial invertebrates farming for food production, safety aspects and comparative analysis with other edible species are discussed.